The Implementation of Flipped Classroom in Improving Students' Writing Skills at The University of Brawijaya - Siswanto, Ridwan Adi (Jurnal Ilmu Pendidikan, 2021)
This study aims to investigate the effect of the flipped classroom on students' writing skills, active involvement in the classroom, and students' perception of flipped classrooms. By using a pre-experimental design, this study involved 27 fourth-semester students of Class B, Educational English Department of the Faculty of Cultural Studies, University of Brawijaya Malang, in the academic year 2019-2020. The participants were selected through cluster random techniques. The data were collected from pretest and posttest questionnaires, field notes, and video documentation. The results suggest that the student's writing skills were improved by 26.222 mean scores by using flipped classrooms, from 52.44 scores of pretest to 78.67 scores in the posttest. Besides, flipped classroom method has been observed to help the student be more active in self-learning online. The student also presents a positive perception towards flipped classrooms in improving writing skills, with score of 73.56